ROUTINE HAND-HYGIENE COMPLIANCE BY HOSPITAL STAFF AND SOME ASSOCIATED FACTORS AT SON LA PROVINCIAL GENERAL HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the situation of routine hand-hygiene compliance by hospital staff and someassociated factors at Son La Provincial General Hospital in 2022.Methods: A cross-sectional study was conducted with a sample size of 350 hospital staff.Results: The proportion of compliance with routine hand-hygiene of the medical staff at the hospitalaccounted for 60.6%. There was a correlation between participation in infection control training(OR=0.66; 95% CI: 0.5-0.9; p
Keywords: Routine hand-hygiene compliance, associated factor, hospital staff.